La naturaleza como acontecimiento El señuelo de lo posible - Debaise, Didier (New Metaphysics, 2022)
We have entered a new era of nature. What remains of the borders of modern thought that separated the living from the inert, subjectivity from objectivity, the apparent from the real, the value from facts, and the human from the non-human? Can the great oppositions that presided over the modern invention of nature preserve their coherence? In Nature as Event, Didier Debaise argues that new narratives and cosmologies are needed to rearticulate what has so far remained separate. Following William James and Alfred North Whitehead, Debaise presents us with a pluralistic way of approaching nature. What would happen if we attribute subjectivity and potentiality to all beings, both human and non-human? Why could we not think of the aesthetic and affective dimension as the fabric that links everything that exists? And what if the senses of importance and value were no longer understood as exclusively limited to the human? Translation by Laureano Ralón and Román Suárez